Parking Space Requirement Analysis at the University of North Sumatra General Hospital - Susila, Hermanta; Hasibuan, Gina Cynthia Raphita; Anas, Ridwan (ASTONJADRO, 2025)
Hospitals are places of activity that provide vital services to the community. In reality, most hospitals are faced with the problem of providing parking facilities. One of them is the difficulty of providing parking space facilities that match the actual level of demand. The aim of the research is to obtain information on parking demand by modelling car and motorcycle parking. The methods used are linear regression and non-linear regression methods. On poly days for car parking demand with the equation: Y₁=8.166×10-89× 41.386 X₁ and motorcycles with the equation: Y₂=7553.126-1112960.605/X₁, Y₂=6033.071-1392502.512/X₂, and Y₂=6389.337-1570378.771/X₃. On non-poly days for car parking demand with the equation: Y₁=868,250-3,250X₂ and motorcycles with the equation: Y₂=-457,000 + 6,000X₄.